UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BUNGA KECOMBRANG (Etlingera elatior (Jack) R. M.Sm.) TERHADAP BAKTERI Propionibacterium acnes - Yulistia Budianti Soemarie; Anita Apriliana; Achmad Kadri Ansyori; Pipih Purnawati (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
Acne is one of the skin diseases that disturbs the appearance especially of teenagers. Some types of bacteria that cause acne is Propionibacterium acnes. An alternative natural ingredient that can be used to treat acne is kecombrang flowers (Etlingera elatior (Jack) R.M.Sm.). The purpose of this study was to determine whether the kecombrang ethanol extract has antibacterial activity against the bacteria that caused acne, and to know the effective concentration of the ethanol extract of the kecombrang flower on the bacteria that caused the acne. The research conducted was experimental research. The stages of the study began from the determination of the sample, the manufacture of simplicia powder, extraction of kecombrang flowers using the maceration method, phytochemical screening and antibacterial activity test using the disc diffusion method. The concentrations of extract used in the testing of antibacterial activity were 20%, 40%, 60% and 80%. The results showed that the ethanol extract of the kecombrang flower contained secondary metabolites in the form of flavonoids and saponins. The results of the testing of the antibacterial activity showed that the ethanol extract of the kecombrang flowers had a medium activity at a concentration of 80% against the Propionibacterium acnes bacteria with a inhibition zone of 7,67 mm. Keywords: Kecombrang flowers (Etlingera elatior (Jack) R.M.Sm.), Antibacterial activity test, Propionibacterium acnes